Engineering cell–cell communication networks: programming multicellular behaviors - Toda, Satoshi; Frankel, Nicholas W; Lim, Wendell A (Current opinion in chemical biology, 2019)
Cell–cell communication governs the biological behaviors of multicellular populations such as developmental and immunological systems. Thanks to intense genetic analytical studies, the molecular components of cell–cell communication pathways have been well identified. We also have been developing synthetic biology tools to control cellular sensing and response systems that enable engineering of new cell–cell communication with design-based regulatory features. Recently, using these molecular backgrounds, synthetic cellular networks have been built and tested to understand the basic principles of multicellular biological behaviors. These approaches will provide new capabilities to control and program desired biological behaviors with engineered cell–cell communication to apply them toward cell-based therapeutics.